Analysis of a radially graded rod under tension - Ng, Jovan Jing Rong (Nanyang Technological University, 2022)
With the advancement of materials, functionally gradient materials have been a key research topic for improving currently available material in the field of engineering. The use of such material avoids stress concentration due to the discontinuity of traditional composite materials while still maintaining its strengths. In this paper, an analysis of a functionally graded rod in the radial direction is placed under tension axially to understand the displacement at every point of the rod. The material gradient of the rod is being studied by implementing varying different material gradients and analyzing the results. The approach is to solve the equilibrium equations both analytically and numerically to express it in its stress and displacement.